Association of high-sensitivity C-reactive protein to albumin ratio with all-cause and cardiac death in coronary heart disease individuals: A retrospective NHANES study. - Shangxun Zhou; Miaohan Qiu; Kexin Wang; Yixuan Duan; Daoshen Liu; Ying Xu; Xuefei Mu; Jing Li; Yi Li; Yaling Han (PLoS ONE)
Background This research aimed to explore the association of high-sensitivity C-reactive protein to albumin ratio (CAR) with death events in community-based patients with coronary heart disease (CHD). Methods 624 CHD participants were followed for 36 months using data from the 2015-2018 National Health and Nutrition Examination Survey (NHANES). The CAR was dichotomized at 0.075 mg/g to stratify inflammation levels. Relationships between CAR, high-sensitivity C-reactive protein (hsCRP), albumin (ALB) and all-cause and cardiac death in all participants and subgroups were analyzed using restricted cubic spline (RCS), Kaplan-Meier survival curves and Cox proportional hazards models. Results Both CAR and hsCRP showed positive correlations with all-cause and cardiac death risk while ALB exhibited a U-shaped correlation with all-cause death risk but a negative correlation with cardiac death risk. The high-CAR group had higher risks of all-cause (P = 0.04) and cardiac death (P = 0.02). The hazard ratios (HR) (95% confidence intervals (CI)) for all-cause death was 1.77 (1.15-2.74) (P = 0.010), while it was 2.99 (1.44-6.22) (P = 0.003) for cardiac death. No significant interaction was observed in subgroup analyses. Conclusions A CAR threshold of 0.075 mg/g effectively distinguished between high and low inflammation risks. Elevated CAR significantly increased the risk of all-cause and cardiac death in community CHD patients.